Discrimination, social capital, and financial constraints: The case of Viet Nam - Tho Pham; Oleksandr Talavera (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper examines the relationship between gender, social capital, and access to finance of micro, small, and medium enterprises in the manufacturing sector in Viet Nam. Our dataset is from the 2011, 2013, and 2015 waves of the Micro, Small, and Medium Enterprise Survey in Viet Nam. Using the Heckman technique to control for sample selection bias, the data do not provide evidence for discrimination against female-owned enterprises in the formal lending market. Specifically, female entrepreneurs have a higher probability of getting a loan and they pay lower interest rates in comparison with male entrepreneurs. No discrimination in formal credit markets may arise from the preference for informal loans over formal loans - that is, entrepreneurs tend to borrow informal loans before applying for formal ones. Further analysis shows that social capital could facilitate loan applications: firms that have a closer relationship with government officials and other business people can get loans of longer duration.
Keywords: G21; J16; L26; 330; entrepreneurship; financial constraints; gender; discrimination